Social and ethical issues in genetic counselling - Hodgson, Shirley (Henry Stewart Talks, 2021)
Principles of genetic counselling, Confidentiality and ethical issues in genetic counselling, Ownership of genetic information, The role of genetic counsellors, Genetic testing in children and during pregnancy, Genetic testing of unaffected people, Clinical relevance of genetic testing, Genome editing and regulations, Avoiding eugenic thinking